PERENCANAAN REHABILITASI SALURAN INDUK DAERAH IRIGASI CIBINUANGEUN DI KABUPATEN LEBAK PROVINSI BANTEN - Restu Candra; Rino Dwi Sadi; Ma'ulfi Kharis Abadi (Journal of Sustainable Civil Engineering (JOSCE), 2021)
Irrigation is an effort to provide and regulate water for agricultural land. The main objective of this study is to plan the rehabilitation of the main channel of Cibinuangeun irrigation area, Lebak Regency, Banten Province. The main channel serves to carry water from the main network to the secondary channel and tertiary plot. The material can be made of masonry, concrete or masonry and concrete. The Cibinuangeun main channel relies on a water source from the Cibinuangeun river through the Cibinuangeun weir building. The Cibinuangeun Irrigation Area has a functional area 2570 ha. The condition of the Cibinuangeun main canal currently has a lot of damage, which results in water drainage being not optimal so it is necessary to plan for rehabilitation by directly examining the condition of the canals at the location to determine the volume of damage and calculate the cost of rehabilitation on the channel. The research method used is the Irrigation Planning Criteria issued by the Ministry of Public Works, Directorate General of Water Resources as the basis for standard irrigation planning. The results showed that the trapezoidal trunk channel and the current available flow rate were not in accordance with the initial planning of the Cibinuangeun main channel construction, due to sedimentation and damage to the walls and floor of the leaking channel. The level of damage to the main line reached 47,37% of a total trunk length of 950 meters. The planned cost required for the rehabilitation of the Cibinuangeun main channel is four hundred seventy million four hundred thousand rupiah.